HOW TO CREATE SPEAKING POLITENESS IN ELEMENTARY SCHOOL - winda sari; arma nila; Hasnah Siahaan; Isma Yunita; Syariah Hafizhoh (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2022)
This research aims to describe and analyze the form of politness language in conversation at classroom. Interaction between the students and teachers. The approach which is used qualitative descriptive. This research activity uses data collection methods, namely competent free involvement methods, and notes. Data of this research is the language expressions in the form of words and sentences of the speakers. The data source of this research is used oral data source in the form of speech event between the speakers, namely between the studets to their teachers. The politeness language for an interction with the teachers in classroom learning is very dominant in the three modes of speech, they are 1) request; 2) application; and 3) expect. Asking is a directive politeness act that has the goal of expecting the speech partner to be given something as requested by the speaker.